Identifying Thyroid Carcinoma-Related Genes by Integrating GWAS and eQTL Data - Shen, Fei; Gan, Xiaoxiong; Zhong, Ruiying; Feng, Jianhua; Chen, Zhen; Guo, Mengli; Li, Yayi; Wu, Zhaofeng; Cai, Wensong; Xu, Bo (Frontiers in Cell and Developmental Biology, 2021)
Thyroid carcinoma is the most common endocrine malignancy. The incidence rate of thyroid cancer has increased rapidly in recent years. The occurrence and development of thyroid cancer is highly related to the massive genetic and epigenetic changes. Therefore, it is essential to explore the mechanism of thyroid cancer pathogenesis. Genome-Wide Association Studies (GWAS) have been widely used in various diseases. Researchers have found multiple single nucleotide polymorphisms (SNPs) are significantly related to the thyroid carcinoma. However, the biological mechanism of these SNPs is still unknown. In this paper, we integrated GWAS with expression quantitative trait loci (eQTL) in both thyroid and blood to explore mechanism of mutations and causal genes of thyroid cancer. Finally, we found rs1912998 regulates the expression of IGFALS and HAGH in thyroid, which is significantly related to thyroid cancer. In addition, KEGG shows that these genes participant multiple thyroid cancer-related pathways.